Optimization of Carbon Fiber-Reinforced Polymer (CFRP) Configuration for Enhanced Flexural Performance in Strengthened Concrete Beams - Eyad Alsuhaibani (Buildings)
This study investigates the optimization of carbon fiber-reinforced polymer (CFRP) sheet dimensions and anchorage configurations to enhance the flexural performance of concrete beams while maintaining cost-effectiveness. Eight beam specimens, incorporating variations in CFRP length, width, and anchorage systems, were tested under a three-point bending setup. A systematic approach was employed to evaluate key structural performance metrics, including normalized ultimate load capacity, energy absorption index, and relative deflection index, while minimizing material usage. The results revealed that the W.L.2U configuration, featuring full-length and full-width CFRP sheets with double U-wraps, delivered the highest performance, achieving a 161% increase in ultimate load capacity, an 822% improvement in energy absorption, and superior deflection. Comparative analysis highlighted critical trade-offs between material efficiency and performance, with configurations with full-width and half-length, such as W.0.5L, balancing efficiency and load-bearing enhancements. This study demonstrates that optimizing CFRP configurations, particularly in terms of length, width, and anchorage, is essential for maximizing structural performance while minimizing material usage, offering practical insights for cost-effective and performance-driven structural retrofitting applications.